Hepatic perivascular epithelioid cell tumor resembling hepatic adenoma and hepatocellular carcinoma on preoperative imaging: a case report - Zhu, Dongling; Song, Shuang; Wang, Dongdong; Kuang, Dong; Cheng, Siyuan; Zhou, Jianyuan; Zou, Sijuan (Frontiers in Oncology, 2024)
Perivascular epithelioid cell tumor (PEComa), an uncommon mesenchymal neoplasm, arises from specialized perivascular epithelioid cells exhibiting distinct features of smooth muscle and melanocytic differentiation with unpredictable behavior. PEComa tends to occur more commonly in the uterus and kidneys, their occurrence in the liver is exceedingly rare. We presented a case of a 29year-old woman with hepatic PEComa and evaluated the tumor with MRI, integrated 18 F-FDG, and 68 Ga-fibroblast activation protein inhibitor (FAPI) PET/CT scans at presentation. The patient had a history of intermittent utilization of oral contraceptive drugs for several years. An abdominal ultrasound in physical examination from an outside institution revealed a mass in the liver. A contrast-enhanced abdominal MRI revealed restricted diffusion on diffusion-weighted imaging (DWI) and rapid contrast enhancement and washout patterns in the hepatic lesion, suggesting hepatic adenoma (HA) or hepatocellular carcinoma (HCC). Further assessment was carried out using 18 F-FDG and 68 Ga-FAPI PET/CT scans. The hepatic lesion was non-FDG avid, whereas increased tracer uptake was observed on the 68 Ga-FAPI PET/CT. Subsequently, laparoscopic partial resection of liver segment V was performed. Immunohistochemical analyses demonstrated positive staining for HMB45, Melan-A, and SMA while showing negative results for AFP, Glypican-3, Hepatocyte, and Arginase-1. The results were indicative of a hepatic PEComa diagnosis being by these findings. We also review the current literature on the clinical characteristics, pathological features, and challenges in the diagnosis of hepatic PEComa.